Great communication secrets of great leaders - Baldoni, John (New York : London : McGraw-Hill, 2003)
A groundbreaking guide to mastering the most important leadership skills. Great Communication Secrets of Great Leaders gives anyone from managers to executives an unparalleled opportunity to do just that. John Baldoni explores the communication styles of many of the world's most influential leaders and extracts powerful lessons that leaders of all stripes can use to improve their communication skills and overall leadership effectiveness. Drawing upon his years of experience as a top leadership consultant, visionary and coach, Baldoni. Reveals the communications secrets of Jack Welch, Rudy Giuliani, Colin Powell, Peter Drucker, Winston Churchill, Steve Jobs, Katharine Graham, and many other influential leaders. Distills the proven communication techniques of today's greatest leaders into core strategies and step- by-step solutions. Develops guidelines for making the most of computer-aided presentations, videoconferencing, and other new technologies.
Part I. Developing the leadership message : What is leadership communications? : Winston Churchill: The lion who roared for his people -- Who are you ... and why are you talking to me? : Rudy Giuliani: leading with hope -- Developing the leadership message : Katherine Graham: leading from within -- Leadership communications planning : Shelly Lazarus: a brand of leadership -- Leading with e-communications : Peter Drucker: management unbound -- Structuring the stand-up leadership presentation: Colin Powell: the centered vision -- Part II. Delivering the leadership message : Assessing your audience : Bill Veeck: master promoter -- Delivering the message : Jack Welch: the strategic communicator -- Part III. Sustaining the leadership meesage : Connecting with people beyond words : Mother Theresa: a life of healing ; George C. Marshall: fhe great mobilizer -- Coaching: one-to-one leadership communication : Vince Lombardi: the teacher as coach ; Harvey Penick: Lessons from a pro -- Making certain the message sticks : Rosabeth Moss Kanter: Doyenne of change -- Leader as storyteller : Oprah Winfrey: Life as a story -- Appendix : Putting it all togetther ; Summary notes ; Action steps ; Leadership communications action planner.
Keywords: Communication in management; Leadership